The Salesperson's Role in the Realisation of the Potential Value of a Business Buyer-Seller Relationship - Zhang, Annie Liqin (Auckland University of Technology, 2011)
This research investigates which salespeople’s relationship activities in a business-to-business buyer-seller relationship influence the level at which the buyer’s resources are accessed and used for the benefit of both the seller and the buyer. The study then examines how these activities are connected to the relationship performance for the seller directly as well as indirectly through the availability of the buyer’s resources. The topic is important as firms rely heavily on their salespeople to achieve better customer relationship performance, and the value of a relationship lies in the way the resources of the buyer and the seller are combined and utilised for value creation for both firms. In this thesis, this inter-firm resource combination and usage process is referred to as “co-creation”, as researchers note that, in business-to-business relationships, value is co-created through the integration of the two firms’ resources (Vargo & Lusch, 2011). Existing research has been focusing on the role salespeople play in obtaining internal resources for serving customers. The role the buyer’s resources play in value realisation for the seller, has not been specifically addressed, especially how the availability of a buyer’s resources can be influenced by the salesperson’s relationship activities. Building on the ARA (activity-resource-actor) structure of the network theory (Håkansson & Snehota, 1995), this research proposes two constructs, the availability of the buyer’s resources and the salesperson’s relationship focus level, and establishes the structure of the conceptual framework of the current research. The salesperson’s relationship focus level refers to the level of attention a salesperson allocates to gaining access to a buyer’s resources and making good use of the resources for realising the potential value of the relationship for the seller. It is a higher-order construct that directs the salesperson’s relationship activities and is assessed by the intensity of the salesperson’s activities that are identified in this research as relevant to the availability of the buyer’s resources. A mixed-method research design is used to develop the two constructs. Based on the literature review, in-depth interviews are used first to further clarify the domains of the two constructs and to generate the measures. Then quantitative methods test the validity of the two constructs and the research model. Structural equation modelling is used to analyse the survey responses. The fit indices results show that the structural model fits well to the data. The validities of the constructs in the research model are well supported. The salesperson’s relationship focus level has six reflective dimensions: which correspond to the intensity levels of the six relationship activities including learning about the seller’s resources, learning about the buyer, customer contact, service, selling, and coordination. The salesperson’s relationship focus level has a significant and positive influence on both the availability of the buyer’s resources and the relationship performance for the seller. In addition, the effect of the salesperson’s relationship focus level on the relationship performance for the seller is partially influenced by the availability of the buyer’s resources. This research makes three contributions: (1) measure development of the two constructs, which are the availability of the buyer’s resources and the salesperson’s relationship focus; (2) empirically testing the validity of these two constructs and finding associations between these two and relationship performance for the seller; (3) the mixed-methods approach to the scale development. The results show that the realisation of relationship value requires significant efforts in improving the knowledge of how the buyer’s and the seller’s resources can be combined and used, engaging the buyer in relevant dialogue, exploring the opportunities that are associated with the use of both firms’ resources, and coordinating the two firms’ activities and other relevant third parties’ activities.
Keywords: Actor-activity-resource; Salespeople' s activities for relationship value co-creation; Availability of the buyer's resources for relationship value co-creation; Mixed-methods; Scale development